Faktor Determinasi Kualitas Audit: Pada Perusahaan BUMN di Indonesia Tahun 2015-2019 - Friscilia Meila Anggina; Charoline Cheisviyanny; Dovi Septiari (Universitas Negeri Padang, 2021)
This study aims to examine the effect of audit quality determination factors which consist of restatement, small profit, prior roa meet, going concern opinion and type 1 error going concern opinion on audit quality. This research was conducted on BUMN companies in Indonesia in 2015-2019 and the research sample was determined using the purposive sampling method so that 46 sample companies were obtained. The results show that companies that do restatement do not have a worse audit quality than those that do not restate, companies that are categorized as small profit do not have audit quality that are worse than those that are not categorized as small profit, companies that are categorized as prior-roa meet do not have audit quality that is worse than those who are not categorized as prior roa meet, auditors who provide going concern opinions do not have better audit quality than those who do not provide going concern opinions and auditors who make type 1 errors going concern opinions do not have worse audit quality than those who do not commits a type 1 error of going-concern opinion.